STRENGTHENING ELDERLY HEALTH PROMOTION: A COMMUNITY-BASED APPROACH TO DIABETES MELLITUS PREVENTION - Dwi Uswatun Sholikhah; Eliza Zihni Zatihulwani; Asri Kusyani; Yusiana Vidhiastutik; Enny Puspita; Aditya Nuraminudin Aziz; Kusuma Wijaya Ridi Putra (Journal of Indonesian Public Health Service, 2026)
Diabetes mellitus is a growing public health concern, particularly among older adults, due to age-related metabolic changes and lifestyle factors. In Indonesia, the increasing prevalence of diabetes highlights the need for effective community-based preventive strategies, especially through health promotion at the posyandu lansia level. This study aimed to strengthen elderly health promotion by implementing a community-based health education program to improve knowledge and awareness of diabetes mellitus prevention. A community service-based intervention was conducted on January 20, 2026, in Sentulan Hamlet, Bongkot Village, Peterongan District, Jombang. The participants were elderly individuals attending the local posyandu lansia. The intervention included health education sessions on diabetes mellitus, its risk factors, symptoms, and prevention through a healthy lifestyle, followed by free blood glucose screening. Educational methods included lectures, discussions, and distribution of leaflets. Evaluation was conducted through participant engagement and responses during the session. The program was well received by participants, who actively engaged in discussions and demonstrated increased understanding of diabetes prevention. The blood glucose screening also provided early detection opportunities and increased awareness of individual health status among the elderly. The combination of education and screening proved to be an effective strategy in enhancing health awareness. Community-based health education combined with blood glucose screening is an effective approach to strengthening diabetes prevention efforts among the elderly. This model can be implemented in similar community settings to promote healthy aging and reduce the risk of chronic diseases. The evaluation process was conducted using observational assessment, participant engagement monitoring, interactive question-and-answer sessions, and feedback from elderly participants and community cadres.